Coomaniella sunfengyii sp. nov., a new species from Fujian, China (Coleoptera: Buprestidae: Coomaniellini) - Liao, Zhi-Yu; Su, Rong-Xiang; Qi, Zhi-Hao; Tang, Chen-Sheng; Cai, Shou-Ping; Song, Hai-Tian (Zootaxa, 2023)
A new species Coomaniella sunfengyii Liao, Su, Qi & Song, sp. nov. from Fujian Province, China, is described and placed in the Coomaniella macropus species-group. The description, illustrations, host plant information and diagnostic characters of the new species are provided.